PENGARUH TINGKAT PEMBIAYAAN MUDHARABAH TERHADAP TINGKAT RASIO PROFITABILITAS PADA KOPERASI JASA KEUANGAN SYARIAH (KJKS) MANFAAT SURABAYA - Imam Buchori; Aji Prasetyo (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2014)
Many financial institutions those were born with the Shariah-based in Indonesia–including non-bank financial institutions, among them are Islamic insurance, Shariah pawnshop, Shariah financial services cooperatives, and more. Shariah-compliant financial services cooperatives (KJKS) Manfaat Surabaya is still classified as